2019
DOI: 10.3389/fnins.2019.00505
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Upregulates Teneurin-3 Expression via Canonical and Non-canonical Wnt Pathway Crosstalk

Abstract: Teneurins (Tens) are a highly conserved family of proteins necessary for cell-cell adhesion. Tens can be cleaved, and some of their proteolytic products, such as the teneurin c-terminal associated-peptide (TCAP) and the intracellular domain (ICD), have been demonstrated to be biologically active. Although Tens are considered critical for central nervous system development, they have also been demonstrated to play important roles in adult tissues, suggesting a potential link between their deregulation and vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…This work not only demonstrate the involvement of Wnt signaling in regulating Ten-3 expression but also revealed that Wnt3a (a canonical Wnt ligand) increases the expression of Ten-3 through a mechanism dependent on the secretion and activity of Wnt5a (a noncanonical ligand). Although the work raises new questions, the results seem to demonstrate the upregulation of Ten-3 by Wnt signaling and suggest that Ten-3 modulation is possible because of crosstalk between the canonical and noncanonical Wnt pathways (52).…”
Section: Discussionmentioning
confidence: 92%
“…This work not only demonstrate the involvement of Wnt signaling in regulating Ten-3 expression but also revealed that Wnt3a (a canonical Wnt ligand) increases the expression of Ten-3 through a mechanism dependent on the secretion and activity of Wnt5a (a noncanonical ligand). Although the work raises new questions, the results seem to demonstrate the upregulation of Ten-3 by Wnt signaling and suggest that Ten-3 modulation is possible because of crosstalk between the canonical and noncanonical Wnt pathways (52).…”
Section: Discussionmentioning
confidence: 92%
“…Teneurin 3 belongs to a highly conserved family of proteins and is necessary for various functions, including cell adhesion, cytoskeleton interaction, and calcium binding [ 17 , 18 ]. Previous studies revealed a novel mutation in TENM3 (OMIM * 610083) , which co-segregated in all severely affected members in a three-generation family from Philadelphia.…”
Section: Discussionmentioning
confidence: 99%
“…WNT3A, β-catenin, and pGSK3β are components of the Wnt signaling pathway [ 24 ], and the activation of this pathway reportedly induces EndoMT [ 24 , 25 ]. WNT3A is a Wnt protein that activates the canonical Wnt pathway and to be bioactive as determined by TCF/LEF [ 26 ]. WNT3A involved in neural crest cell differentiation and hCECs are derived from neural crest [ 27 ].…”
Section: Discussionmentioning
confidence: 99%